Passively Q-switched erbium-doped fiber laser utilizing lutetium oxide deposited onto D-shaped fiber as saturable absorber - Jafry, A.A.A.; Kasim, N.; Munajat, Yusof; Yusoff, R.A.M.; Rusdi, Muhammad Farid Mohd; Mahyuddin, Mohamad Badrol Hisyam; Harun, Sulaiman Wadi; Arof, Hamzah; Apsari, Retna (Elsevier, 2019)
We managed to produce a stable Q-switched pulse laser operating at 1563 nm using Lutetium (III) oxide (Lu2O3) material as a saturable absorber (SA). The Lu2O3 was deposited onto a D-shaped optical fiber and inserted into an erbium-doped fiber laser (EDFL) cavity for pulse generation. The D-shaped fiber was prepared by polishing wheel technique using rough and fine sandpapers to obtain a smooth surface and thus ensure an efficient light-matter interaction inside the SA. The proposed Q-switched EDFL generated pulses with duration as short as 11.84 μs at a repetition rate of 19.7 kHz. The Q-switched laser output was stable within the pump power of 68 mW–96 mW with the corresponding pulse energy and output power of 0.16 μJ–0.18 μJ and 2.76 mW–3.49 mW respectively. The signal-to-noise ratio was around 46.26 dB, which indicates the stability of the laser. The results show that the proposed Lu2O3 SA based on D-shaped fiber is suitable for realizing a portable Q-switched light source. © 2019 Elsevier GmbH